2020
DOI: 10.3390/ijms21072495
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine Deiminase of Porphyromonas gingivalis Modulates the Interactions between Candida albicans Biofilm and Human Plasminogen and High-Molecular-Mass Kininogen

Abstract: Microorganisms that create mixed-species biofilms in the human oral cavity include, among others, the opportunistic fungus Candida albicans and the key bacterial pathogen in periodontitis, Porphyromonas gingivalis. Both species use arsenals of virulence factors to invade the host organism and evade its immune system including peptidylarginine deiminase that citrullinates microbial and host proteins, altering their function. We assessed the effects of this modification on the interactions between the C. albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 87 publications
(70 reference statements)
0
16
0
Order By: Relevance
“…In addition to host endogenous PADs, enzymes synthesized and released by an anaerobic periodontal bacterium P. gingivalis (PPAD) may also appear in the host organism. For C. albicans , it was shown that seven moonlighting proteins Eno1, Adh1, elongation factor 1-alpha 1, Tdh3, heat shock proteins Ssa1 and Ssa2 and ATPase 1 of the plasma membrane could be citrullinated by PPAD [ 133 , 134 ]. The ability to citrullinate fungal moonlighting proteins may affect the disclosure of epitopes that have no immune tolerance, which consequently induces antigen production and autoimmunity.…”
Section: Acquired Functions (Moonlighting) Of Atypical Cell Wall Pmentioning
confidence: 99%
“…In addition to host endogenous PADs, enzymes synthesized and released by an anaerobic periodontal bacterium P. gingivalis (PPAD) may also appear in the host organism. For C. albicans , it was shown that seven moonlighting proteins Eno1, Adh1, elongation factor 1-alpha 1, Tdh3, heat shock proteins Ssa1 and Ssa2 and ATPase 1 of the plasma membrane could be citrullinated by PPAD [ 133 , 134 ]. The ability to citrullinate fungal moonlighting proteins may affect the disclosure of epitopes that have no immune tolerance, which consequently induces antigen production and autoimmunity.…”
Section: Acquired Functions (Moonlighting) Of Atypical Cell Wall Pmentioning
confidence: 99%
“…Moreover, these three fungal proteins, Als3, Mp65, and Eno1, were identified as citrullinated by the bacterial enzyme—peptidylarginine deiminase (PPAD)—during the interactions of C. albicans ATCC 10231 with P. gingivalis at a ratio of 1:10 in mixed biofilm formed for 24 h in the simultaneous model of interaction in RPMI 1640 medium. Additionally, also other surface-exposed candidal moonlighting proteins were prone to this modification, including Hxk2, Pgk1, Adh1, pyruvate decarboxylase (Pdc1), and glyceraldehyde-3-phosphate dehydrogenase (Tdh3) ( Karkowska-Kuleta et al., 2018 ; Karkowska-Kuleta et al., 2020 ). This modification may influence their role in biofilm, as it was pointed out that citrullination by PPAD is important in the process of mixed biofilm formation because the adhesion of the P. gingivalis mutant strain deprived of PPAD was significantly lower than that observed for the wild-type strain ( Karkowska-Kuleta et al., 2018 ).…”
Section: Fungal Virulence Factors Important For Biofilm Community Formationmentioning
confidence: 99%
“…This modification may influence their role in biofilm, as it was pointed out that citrullination by PPAD is important in the process of mixed biofilm formation because the adhesion of the P. gingivalis mutant strain deprived of PPAD was significantly lower than that observed for the wild-type strain ( Karkowska-Kuleta et al., 2018 ). In addition, also the interaction with the host proteins may be altered since the citrullination of surface-exposed fungal proteins resulted also in the reduced binding of human plasminogen ( Karkowska-Kuleta et al., 2020 ).…”
Section: Fungal Virulence Factors Important For Biofilm Community Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that gingipains might also play a part for the increased risk of oral cancer in patients with periodontitis—this was associated with the inactivation of SPINK6, an inhibitor of kallikrein activation in the epithelium, probably resulting in augmentation of kinins, which are recognized mitotic mediators [ 67 ]. Remarkably, it was found that formation of complex oral biofilms between P. gingivalis and Candida albicans is dependent on the action of gingipains and peptidylarginine deiminase, which in turn leads to kinin citrullination, changing the affinity for kinin receptors, what finally contributes for pathogen escaping mechanisms [ 68 ]. Altogether, literature evidence clearly highlights a relevant role for kinins and their receptors in the pathogenesis of periodontitis.…”
Section: Bacterial Infections and Kininsmentioning
confidence: 99%